Utilization of A Website-Based Industrial Practice Supervision System (Prakerin) During Pandemic - Supardi, Supardi; Amir Alkodri, Ari; Sujono, Sujono; Rian Chrisna Putra, Rendy (STMIK Bina Sarana Global, 2021)
Increasing the competence of vocational students to be able to enter the field is the first goal for the quality of every major level school. The supervisory system for monitoring field work practices at the agency is to monitor, control the activities and activities of students where the completion of reports is one of the important requirements in implementing field work practices in research places of companies or agencies, this supervision system effort occurs because most students come from regions which is far from home so that it requires boarding and the number of students who commit fraud by not attending / coming to companies or research institutions, especially when the current pandemic is an excuse for students. In this study using the direct field observation method, interviews with external supervisors, laboratory assistants and students, while the implementation uses the PHP programming language and MySQL database. The results of the student supervision system in implementation activities for 3 months which can have a positive impact on the use of supervising teachers, schools and internship students in completing reports during the pandemic.